(untitled) (European Journal of Marketing and Economics, 2023)
Purchasing behavior of consumers is a complex term that studies a customer’s mind and behavior pattern. Customers’ buying habits are most affected by how well a brand performs and how consumers react to it. Knowing the importance of water in our everyday lives, this study aims to determine which factors influence consumers’ buying decisions when choosing one bottled water brand over another. The factors considered are brand performance, brand response, consumer satisfaction, and purchasing behavior. An empirical analysis was employed to understand and explain the effect these brand factors have on purchase behavior. The survey was applied to a sample size of 303 citizens of Durrës, one of Albania’s biggest cities. For testing each hypothesis raised in the study, the statistical analysis consisted of reliability tests, quantitative statistics, and regression analysis. A positive relationship was identified between each brand-related factor when deciding on purchasing a particular brand of bottled water. Consequently, brand-related factors such as brand performance, brand response, and consumer satisfaction are crucial in determining customers’ purchasing behavior. This study will fill a gap in the literature on this subject in Albania and provide bottled water companies with the knowledge they need to consider while making various critical business decisions.